Preventive Effects of Vitamin C on Cataracts: In Vivo Study - Andri Yosrizal; Rinda Wati; Muhammad Hidayat (HM Publisher, 2022)
Background: A cataract is a disease caused by various factors, one of which is the aging process. With increasing age, the formation of free radicals will cause pathological reactions in the lens and other toxic compounds, resulting in oxidative reactions. Administration of vitamin C injection as an antioxidant can reduce the reactivity of free radicals caused by oxidative reactions in cataract lenses induced by sodium selenite. This study aims to determine the preventive effect of vitamin C administration on selenite-induced cataracts based on the value of malondialdehyde (MDA) levels. Methods: The experimental study used 30 rats which were then divided into 5 treatment groups (P1, P2, P3, P4, and P5). Lenses were extracted for the measurement of malondialdehyde. The value of MDA levels was then analyzed using the One-way ANOVA statistical test. Results: Statistically, there was no significant difference in MDA levels in each treatment group. Analysis of the difference in mean MDA between the 2 groups showed that the average MDA levels of mice in groups P4 and P5 were relatively lower than P2 and P3, but higher than P1. Conclusion: Giving vitamin C was able to reduce MDA levels (a marker of oxidative stress) better than the group that did not receive vitamin C, but not statistically different.